Environmental Education and Adiwiyata Program Acceleration for Madrasah - Maslikhah Maslikhah; Roudlotul Jannah (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
A comfortable environment will create a conducive learning atmosphere. Therefore, all madrasas are expected to jointly protect the surrounding environment. This paper aims to describe the development of policies in instilling a caring and cultured attitude towards the environment; environment-based curriculum development; development of community-based environmental activities; as well as the development and management of supporting facilities for caring and environmentally cultured schools as an effort to accelerate the adiwiyata program. This qualitative study data at MAN Salatiga was collected through the use of observation to the school environment. Another is by interviewing to the principals and some vices then the students. The other technique is documentation. The results show that the policies implemented as evidence of environmental care include starting with the vision and mission of the madrasa which are then elaborated in the form of practical invitations and suggestions. The invitation is in the form of posters and writing. The form of practical advice is through direct example. In the curriculum, eighteen characters are developed, one of which is caring for the environment. While activities that involve the community are cooperation in tree planting programs and community service at public cemeteries and places of worship. Provision of trash cans and plant pots is the development of facilities and infrastructure.